Competitors matter: How competitors' actions moderate the influence of firm profitability on the prioritization between growth and efficiency increase - Thomas Hutzschenreuter; S. Alexander Borchers; Philippa-Luisa Harhoff (Managerial and Decision Economics, 2021)
Firms have been shown to prioritize between growth and efficiency increase sequentially depending on their level of profitability. Adding arguments from the attention-based view to this discussion, we hypothesize that actions of competitors in the marketplace could moderate this relationship. Using data from business simulations, we specifically test whether the influence of firm profitability on the prioritization decision varies with changes in competitor products' pricing, promotion, and quality. Our analysis reveals that product promotion intensifications of competitors strengthen the positive relationship between firm profitability and the prioritization of growth relative to efficiency increase, whereas product price reductions weaken this relationship.
Keywords: 650